Cash crop or food crop? socioeconomic and geopolitical factors affecting smallholder farmer crop selection in times of crisis in southwestern Tajikistan - Zakirova, Aksana; Alff, Henryk; Schmidt, Matthias (Frontiers in Agronomy, 2023)
Tajikistan's agricultural sector, primarily dominated by cotton cultivation, has experienced significant changes since the Soviet era. Although farmers introduced food crops into agricultural production, to ensure food security after the collapse of the Soviet Union in 1991, the government still mandates that cotton cultivation occupies a considerable portion of Tajikistan's limited irrigated land. However, following the recent Covid-19 pandemic crisis, farmers have encountered the need to reassess their agricultural practices based on a range of socioeconomic considerations along with constrained governmental assistance. The investigation herein delves into the decision-making processes of smallholder farmers amidst crisis, with a specific emphasis on the period spanning from 2019 to 2022. The primary objective is to highlight crop selection strategies that effectively address farmers' immediate needs in troubled times against the backdrop of the existing state cotton policy. This research adopts resilience as a conceptual framework to examine the coping strategies of smallholder farmers in the Khatlon region of Tajikistan. Furthermore, research methods include the snowballing technique, to increase the representative sample size, and the gathering of qualitative data from 100 semi-structured interviews, 10 focus groups and personal visits to agricultural fields over the course of four years. The paper not only demonstrates the overall creativity of Tajikistani farmers in growing and selecting crops in this most recent period of crisis, but also points to wealthier farmers' generally greater willingness to adopt technological innovations and gain new knowledge to apply to their crops.